Suppression of neuropathic pain and comorbidities by recurrent cycles of repetitive transcranial direct current motor cortex stimulation in mice - Gan, Zheng; Li, Han; Naser, Paul; Oswald, Manfred; Kuner, Rohini (Scientific reports, 2021)
Transcranial, minimally-invasive stimulation of the primary motor cortex (M1) has recently emerged to show promise in treating clinically refractory neuropathic pain. However, there is a major need for improving efficacy, reducing variability and understanding mechanisms. Rodent models hold promise in helping to overcome these obstacles. However, there still remains a major divide between clinical and preclinical studies with respect to stimulation programs, analysis of pain as a multidimensional sensory-affective-motivational state and lack of focus on chronic phases of established pain. Here, we employed direct transcranial M1 stimulation (M1 tDCS) either as a single 5-day block or recurring blocks of repetitive stimulation over early or chronic phases of peripherally-induced neuropathic pain in mice. We report that repeated blocks of stimulation reverse established neuropathic mechanical allodynia more strongly than a single 5-day regime and also suppress cold allodynia, aversive behavior and anxiety without adversely affecting motor function over a long period. Activity mapping revealed highly selective alterations in the posterior insula, periaqueductal gray subdivisions and superficial spinal laminae in reversal of mechanical allodynia. Our preclinical data reveal multimodal analgesia and improvement in quality of life by multiple blocks of M1 tDCS and uncover underlying brain networks, thus helping promote clinical translation.
Gesehen am 01.07.2021